2006
DOI: 10.1002/kpm.255
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities in early‐phase entrepreneurship

Abstract: The dynamic capabilities perspective has received increasing attention in the field of strategic management research. By focusing not only on the competitive advantage that is provided by a certain resource constellation, but also on the change of firms' resources over time to fit changing business environments, this perspective underlines the strategic importance of innovation. Despite the apparent interest in the dynamics of firm resources, there is still limited empirical evidence for how the strategic matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 50 publications
1
45
0
3
Order By: Relevance
“…Creativity and innovation play a fundamental role in entrepreneurship (Boccardelli & Magnusson, 2006; S. H. Lee & Wong, 2004) and in this respect the respondents felt that they…”
Section: Perceptions Of University Education and Readiness For Entrepmentioning
confidence: 95%
See 1 more Smart Citation
“…Creativity and innovation play a fundamental role in entrepreneurship (Boccardelli & Magnusson, 2006; S. H. Lee & Wong, 2004) and in this respect the respondents felt that they…”
Section: Perceptions Of University Education and Readiness For Entrepmentioning
confidence: 95%
“…In addition to personal traits, factors in the micro and macro environment that can encourage or hinder entrepreneurship have also been investigated (Franco et al, 2010;Franke & Luthje, 2003). Some of these environmental factors are: market structure and dynamics (Boccardelli & Magnusson, 2006;Van Stel, Storey, & Thurik, 2007); access to financing (Sara Carter, Shaw, Lam, & Wilson, 2007;Itani, Sidani, & Baalbaki, 2011a;Kim, Aldrich, & Keister, 2006;Sandhu, Sidique, & Riaz, 2011;Welsh, Memili, Kaciak, & Al Sadoon, 2014); government policy (Ahmad & Xavier, 2011;N. Carter, Brush, Greene, Gatewood, & Hart, 2003;Goby & Erogul, 2011;Minniti, 2008);political and economic stability (Lerner, 2010;Movahedi & Yaghoubi-Farani, 2012;Taylor & Plummer, 2003);culture and society's views on entrepreneurship (C. C. Baughn et al, 2006;C.…”
Section: Entrepreneurial Intention and Female Entrepreneurshipmentioning
confidence: 99%
“…Moreover, large firms in Western Europe are relatively smaller than their typical counterparts in the US. Perhaps our sample included firms that were too small, even if the dynamic capability concept seems useful in entrepreneurial and small firm contexts (Gibcus and Stam, 2012;Boccardelli and Magnusson, 2006). Consequently, in opposition to what has been shown using various firm samples, DD dynamic capability development does not affect the financial performance of smaller firms to a greater extent than it does for larger firms.…”
Section: Figure 3: Interaction Plots Of the Significant Moderating Efmentioning
confidence: 92%
“…We thus excluded the 53 questionnaires wherein respondents indicated that they had launched no DD initiatives. We did not exclude firms from the study based on size or age, as the dynamic capability concept has proven useful in explaining organisational performance even for small entrepreneurial initiatives occupying early stages (Gibcus and Stam, 2012;Boccardelli and Magnusson, 2006). In the end, 125 questionnaires were completed by sales managers, 65 of which were also completed by IT managers from the same firms.…”
Section: Data Collectionmentioning
confidence: 99%
“…Naturally, universities focus on developing their research abilities yet this is often not included when seeking to determine and evaluate their competitive capabilities (Boccardelli & Magnusson, 2006;Helfat & Peteraf, 2003;McEvily & Marcus, 2005;Teece, 2007;Siegel, Waldman, Atwater & Link, 2004), and knowledge creation issues (Noruzi & Vargas-Hernández, 2010). Noruzi and Vargas-Hernández added that there is a need to consider the extent to which scientific research capability in universities contributes in a sufficient way, to its competitive capability.…”
Section: Background and The Issues Of Studymentioning
confidence: 99%